Extracorporeal Life Support for Patients with Acute Respiratory Distress Syndrome: Review - Tülin Akarsu Ayazoğlu; Didem Onk (Galenos Yayinevi, 2015)
Patients with severe acute respiratory distress syndrome (ARDS) is an acute diffuse, inflammatory lung injury, leading to increased pulmonary vascular permeability with hypoxemia and bilateral radiographic opacities, associated with decreased lung compliance. Extracorporeal membrane oxygenation (ECMO) has been used to support primary or secondary diseases causing respiratory or cardiac failures in newborns, children and adults. Patients with severe ARDS are candidates for ECMO therapy. ECMO is a support modality, not a treatment; it is only beneficial in patients whose primary disease is reversible. ECMO complications-which can lead to mortality, morbidity, long-term disability and reduced quality of life-include surgical and organ bleeding, renal and multi-organ failure and central nervous system problems. The aim of this article was to provide a general overview of ECMO use and outcomes patients with severe acute respiratory distress syndrom.